2021
DOI: 10.1186/s43055-021-00433-0
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal tract imaging findings in confirmed COVID-19 patients: a non-comparative observational study

Abstract: Background Corona virus disease 2019 (COVID-19) pandemic—as declared by the World Health Organization—is a major threatening public health problem. At the time of writing, more than 60,000,000 patients and more than 1,500,000 deaths were recorded worldwide. Besides the classical chest symptoms, gastrointestinal tract-related symptoms were noted, like diarrhea, abdominal distention, and hematochezia, adding more difficulties in the diagnosis of the disease. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
2
8
0
1
Order By: Relevance
“…In this study, ischemic small bowel changes were the most common gastrointestinal vascular complication. This matches Abdelmohsen et al [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, ischemic small bowel changes were the most common gastrointestinal vascular complication. This matches Abdelmohsen et al [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…This could be explained by the higher incidence of vascular comorbidities among the older age groups and the loss of the protective role of estrogen in post-menopausal females. It was near that estimated by Abdelzaher et al [ 18 ] which was 63 years. On the other hand, both exceeded that estimated by Saleh et al [ 16 ] which was 43 years.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Details of these studies are shown in Table 1 and online supplementary Table 1 (for all online suppl. material, see www.karger.com/doi/10.1159/000518473 ) [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 …”
Section: Resultsmentioning
confidence: 99%
“…Several extra-pulmonary manifestations of SARS-CoV-2 (COVID-19) have been described, including the neurologic, cardiac, and abdominal manifestations [ 1 ]. The ischemic bowel changes were the most common abdominal complication accompanying COVID-19 [ 2 ]. Acute pancreatitis is one of the rare complications of COVID-19 infection which was seldom found all over the world outside of China, but not in Egypt.…”
Section: Introductionmentioning
confidence: 99%